Experimental Investigation on E-Waste Concrete Using Mineral Admixtures - Thulasirajan K.; Sai Keerthi P.; Lokesh D.; Shiva Shankar Naik N.; Sreekanth Y.; Hemanth M. (E3S Web of Conferences)
Our reliance on electronics, a cornerstone of modern life, comes at a cost. The relentless pace of technological advancement generates mountains of discarded devices, creating the growing problem of electronic waste. This E-waste, if improperly disposed of, can contaminate landfills and release harmful materials into the environment. This study investigates a potential solution: using a portion of e-waste in place of fine aggregate. To improve overall performance, we also incorporate mineral admixtures. Our research aims to understand how both the amount of e-waste and the specific mineral admixtures used influence the final properties of the concrete. We systematically replaced the fine aggregate with e-waste at varying percentages (0%, 10%, 20%, and 30%) and meticulously analyzed the resulting effects. The study identifies 10% e-waste replacement as the optimal level for achieving desirable properties in M20 grade concrete, a commonly used strength classification. This approach offers a two-fold benefit. It tackles the e- waste crisis by providing a sustainable disposal option, and it potentially reduces the construction industry's reliance on virgin resources like natural sand, contributing to a more sustainable future.